'A Matter of Practical Emergency': Herbert Baker, Hope Bagenal, and the Acoustic Legacy of the Assembly Chamber in Imperial Delhi. (2019) - Smyth, Fiona
Abstract: In 1923, at the request of the government of India, the Department of Scientific and Industrial Research (DSIR) in Britain authorised a specialist research stream. Its purpose was to investigate problems in architectural acoustics specifically related to the new Assembly Chamber then under construction in Imperial Delhi. The design, by Sir Herbert Baker, was unusual for its era in that it was refined with recourse to measured data and calculations with a basis in modern physics. The acoustician, or 'consulting architect', was Hope Bagenal, and his appointment by Baker in 1922 marked the first international commission of a British acoustic consultant. This article examines the acoustic design of the Assembly Chamber in Delhi and identifies the inputs of the various individuals, both architects and scientists, involved. Drawing on the archives of Baker and Bagenal, the records of the DSIR and the Guastavino Company, as well as contemporaneous newspaper coverage, it also demonstrates the longer-term implications of the design and construction process at Delhi, including its role in stimulating subsequent government-funded research in architectural acoustics in Britain.